2009
DOI: 10.1590/s1519-566x2009000300017
|View full text |Cite
|
Sign up to set email alerts
|

Flight activity of Sitophilus oryzae (L) and Sitophilus zeamais Motsch (Coleoptera: Curculionidae) and its relationship with susceptibility to insecticides

Abstract: -Insect-pest mobility can infl uence insect susceptibility to the insecticides used to control them. The objective of this work was to evaluate the fl ight activity of Sitophilus oryzae (L) and Sitophilus zeamais Motsch populations reared on corn and wheat grains, and its relationship with insecticide susceptibility. Unsexed adult insects with ages between 10 and 20 days were placed on a plastic tray. A 40-watt incandescent light bulb was positioned at a 50 cm height relative to the tray. Flight activity was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 19 publications
0
10
0
1
Order By: Relevance
“…These correlations are likely to be expressed between and within dispersal‐related phenotypic traits including morphological, physiological, behavioural and life‐history traits. Genetic trade‐offs between functional wings and insecticide resistance (Vasquez‐Castro et al , 2009) or disease resistance (Adamo & Parsons, 2006; Calleri et al , 2006) are examples of deferred survival costs. Investments in flight morphology for long‐distance movements reduces acceleration speed in butterflies, inducing a negative impact on male‐male interactions and subsequent territory‐holding ability (Berwaerts, Aerts & Van Dyck, 2006; Bonte & Van Dyck, 2009; Kemp, Wiklund & van Dyck, 2006).…”
Section: Life‐history Trade‐offs and Feedbacks Among Dispersal Phmentioning
confidence: 99%
“…These correlations are likely to be expressed between and within dispersal‐related phenotypic traits including morphological, physiological, behavioural and life‐history traits. Genetic trade‐offs between functional wings and insecticide resistance (Vasquez‐Castro et al , 2009) or disease resistance (Adamo & Parsons, 2006; Calleri et al , 2006) are examples of deferred survival costs. Investments in flight morphology for long‐distance movements reduces acceleration speed in butterflies, inducing a negative impact on male‐male interactions and subsequent territory‐holding ability (Berwaerts, Aerts & Van Dyck, 2006; Bonte & Van Dyck, 2009; Kemp, Wiklund & van Dyck, 2006).…”
Section: Life‐history Trade‐offs and Feedbacks Among Dispersal Phmentioning
confidence: 99%
“…A ocorrência desta espécie já havia sido relatada em frutas de caroço, como pêssego, ameixa, nectarina, maçã e uva (Salles, 2003;Botton et al, 2005aBotton et al, , 2005bHickel & Schuck, 2005), e está relacionada a falhas no armazenamento do milho (Salles, 2003;Botton et al, 2005b), que é o cereal mais cultivado em pequenas propriedades rurais nas regiões produtoras de pêssego. A maior atividade de voo de S. zeamais em comparação a S. oryzae (Vásquez-Castro et al, 2009) também pode ser determinante para a migração e a ocorrência da espécie em pomares de pessegueiro e macieira.…”
Section: Resultsunclassified
“…The greater susceptibility to fenitrothion when both species were reared on wheat grains would be another hypothesis to explain for these results. Vásquez-Castro et al [35], using the dry film method observed higher susceptibility of both species to fenitrothion when reared on wheat grains, compared to maize. On the other hand, due to the operational characteristics of the treatment, in which the grains were uniformly spread in a thin layer and treated 6 ISRN Agronomy by using a double-jet hydraulic nozzle (60 degree-betweenjets angle), and as to the morphological characteristics of grains, wheat presented a higher specific surface of contact to the drops.…”
Section: Effectiveness Experimentsmentioning
confidence: 95%
“…In Brazil, resistance to organophosphate insecticides was detected in several populations of S. oryzae [7]; but just slightly resistance to one insecticide of this group (chlorpyriphos methyl) was detected in S. zeamais [8,34]. The higher susceptibility of S. zeamais compared to S. oryzae occurs because the first species presents greater flight activity, among other factors, favoring cross-infestation and gene flow, thus preserving the genes of susceptibility to insecticides [35].…”
Section: Effectiveness Experimentsmentioning
confidence: 99%